Children's individual voices are required for adequate management of fear and pain during hospital care and treatment. Issue 2 (4th May 2020) - Kleye, Ida; Hedén, Lena; Karlsson, Katarina; Sundler, Annelie J.; Darcy, Laura
Abstract : Background: Children often report both fear and pain in conjunction with clinical care and treatment. Interventions developed in the field have still not been sufficient to prevent and relieve children's fear and pain. More knowledge, from children's own perspectives, is needed about how they deal with their experiences. Aim: To explore child‐identified strategies that children use to manage fear and pain during needle‐related medical procedures in hospital. Methods: Interviews with children, age 4–12 years, with experience of hospital care were analysed qualitatively using content analysis. Results: Children have self‐identified strategies for dealing with fear and pain during hospital care and treatment. The strategies vary depending on examination or treatment and on how the child felt at that particular day. Children describe what they can do themselves, how adults can empower them and support from surroundings as strategies that give them a choice and a voice. Children wished to have influence, decide when and how information should be given, scream out loud or squeeze something hard, to deal with fear and pain. The results also show that children tried to be brave, gain control and think positively. Something nice to look at and opportunities to play with others also contributed. Conclusions: Strategies vary between children and are used differently on different occasions. Healthcare professionals pose a threat to the child's needs and ability to use their strategies due to lack of knowledge of the child's chosen strategies.